Strong core equivalence theorem in an atomless economy with indivisible commodities - Tomoki Inoue (Bielefeld University, Institute of Mathematical Economics (IMW), 2009)
We consider an atomless exchange economy with indivisible commodities. Every commodity can be consumed only in integer amounts. In such an economy, because of the indivisibility, the preference maximization does not imply the cost minimization. We prove that the strong core coincides with the set of cost-minimized Walras allocations which satisfy both the preference maximization and the cost minimization under the same price vector.
urn:nbn:de:hbz:361-14915
Keywords: C71; D51; 330; Indivisible commodities; Core equivalence; Strong core; Cost-minimized Walras equilibrium; Gleichgewichtstheorie; Core; Marktmechanismus; Unteilbarkeit; Theorie